Gender Representation in Moroccan Secondary School English Textbooks: A Case Study of "Insights into English" - EL HAMMOUCHI, Abdelaziz; BOUTOUTLA, Samia (International Journal of Language and Literary Studies, 2025)
This study examines gender representation in the English as a Foreign Language (EFL) textbook Insights into English, which is currently used in the second year of the Baccalaureate programme in Moroccan public high schools. The research aims to investigate how male and female characters are portrayed and to evaluate the textbook’s role in fostering gender equality. The study contextualizes gender bias and sexism within society and explores the textbook’s influence on learners’ identity construction, with particular emphasis on the depiction of women. Using content analysis, the study systematically analyses the textbook’s content to identify gendered portrayals and potential biases. The findings reveal significant patterns of gender representation, highlighting areas where stereotypes persist. The paper concludes with recommendations for addressing sex bias both within the textbook and in classroom interactions, advocating for pedagogical strategies that promote gender equity and inclusivity. This research contributes to the ongoing discourse on gender sensitivity in educational resources and underscores the importance of critical evaluation of textbooks in shaping learners’ social identities.